Enhanced Optoelectronic Performance and Polarized Sensitivity in WSe2 Nanoscrolls Through Quasi-One-Dimensional Structure - Jinggao Sui; Xiang Lan; Zhikang Ao; Jinhui Cao (Nanomaterials)
Transition metal dichalcogenides (TMDs), such as tungsten diselenide (WSe2), are expected to be used in next-generation optoelectronic devices due to their unique properties. In this study, we developed a simple method of using ethanol to scroll monolayer WSe2 nanosheets into nanoscrolls. These nanoscrolls have a quasi-one-dimensional structure, which enhances their electronic and optical properties. The characterization confirmed their unique structure, and the photodetectors made of these nanoscrolls have high sensitivity to polarized light, with anisotropy ratios of 1.3 and 1.7 at wavelengths of 638 nm and 808 nm. The enhanced light response is attributed to the large surface area and quantum wire-like behavior of the nanoscrolls, making them suitable for advanced polarization-sensitive devices.